ETHICAL AND ENVIRONMENTAL ASSESSMENT OF PERSONALIZED ACTIVITIES AIMED ONPRESERVING THE ENVIRONMENT AND POPULARIZING ENVIRONMENTAL IDEAS - Karpash, О.М.; Bloshchynska, V. A.; Karpash, M. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2024)
An article using the example of a real personality, examines the change in the ecological state of the region through the prism of a ethical attitude to the environment and its impact on the environment. Ethics and ecology are interdependent. This relationship has always been constant and dates back to prehistoric times. With the establishment of ethics as a practical philosophical science, thinkers and prominent personalities were able to clearly define and evaluate human activity in general, and thus describe the impact of humans on nature through the concepts of good and evil. In fact, this interconnection between ethics and ecology was established at that time. An individual changes the world with his or her ideas, descriptions of topical issues, proposals, and practical actions. The quality of a person's influence on the world depends on his or her inner content, spiritual being, which is determined not only by erudition and intelligence, but also by the moral principles that a person professes and considers the norm of a useful and creative life that has a purpose, meaning and purpose for the organisms that inhabit it. The subject of the study is our fellow countryman, Volodymyr Xaveriy Didushytskyi, an outstanding, bright and active personality of the nineteenth century, a world-renowned polymath and philanthropist. He managed to find harmony between theory and practice, combining ethics and ecology with high aesthetics. The purpose of his life-work was to preserve the beauty of life in all its diversity: in nature, art, thoughts, actions and people. He managed to realize a lot of things and his descendants and researchers of his biography have preserved them for future generations. Mr.Volodymyr Didushytskyi proved by his life example that knowledge combined with moral principles brings satisfaction to the owner of charity, as well as to the whole society.